Air leak detection in a pressurized containment building mock-up using elastic guided waves. (January 2022) - Mora, Pierric; Vautrin, Denis; Urso, Guy d'; Letourneur, Stéphane; Chekroun, Mathieu; Longo, Roberto; Tournat, Vincent
Abstract: This article reports an experimental study of the vibrations induced by air leaks in realistic conditions reproducing a leak test of a containment building, such as those routinely conducted to probe the safety of nuclear power plants. The purpose of this work is to assess the effectiveness of a passive acoustic detection method that could assist and accelerate other scanning inspections. Using piezoelectric accelerometers, detection of leak signatures is demonstrated in the 0–20 kHz range. Noise correlation techniques are applied to obtain spectral power densities, maps of amplitudes and beamforming localization which correlate very well with the pressure applied inside the building and with the known locations and flow rates of the main leaks. At applied pressures of 4.2 bars and for concentrated leaks such as point breaks and decimeter long cracks, detection thresholds of about 500–600 L/h flow rates are reached at up to 4–5 m distance by accumulating data during 2 min under silent ambient noise conditions.